1993
DOI: 10.1111/1523-1747.ep12356896
|View full text |Cite
|
Sign up to set email alerts
|

Amyopathic Dermatomyositis: A Review.

Abstract: Jim Gilliam's research interests throughout his career were forced upon better defining the relationships that exist between the cutaneous and systemic manifestations of the rheumatic diseases. Although the majority of his time was spent studying such relationships in lupus erythematosus patients, he was also intensely interested in dermatomyositis (DM) in this regard as well. He was particularly intrigued with the dissociation of the cutaneous and muscular manifestations of this disorder that occasionally occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 14 publications
2
66
0
3
Order By: Relevance
“…Twelve healthy volunteers were also included as control subjects. DM or CADM was diagnosed based on the criteria of Bohan and Peter or following the modified Sontheimer's definitions (15,16). Clinical data, including medical history and physical examination results, were collected upon admission and during followup.…”
Section: Methodsmentioning
confidence: 99%
“…Twelve healthy volunteers were also included as control subjects. DM or CADM was diagnosed based on the criteria of Bohan and Peter or following the modified Sontheimer's definitions (15,16). Clinical data, including medical history and physical examination results, were collected upon admission and during followup.…”
Section: Methodsmentioning
confidence: 99%
“…A myopathic dermatomyositis (ADM) is recognised as a distinct subgroup of dermatomyositis (DM) with the typical skin rash of classic DM, but without muscle involvement [1][2][3][4][5][6]. Several studies have demonstrated that rapidly progressive interstitial lung disease (ILD) with a poor prognosis occurs in patients with ADM [7][8][9][10][11][12].…”
mentioning
confidence: 99%
“…Amyopathic dermatomyositis (ADM) was first described by Pearson (14) and is a disease which only has the cutaneous manifestations of DMwithout any clinical evidence of underlying inflammatory muscle disease. Euwer and Sontheimer (15) discussed that the diagnostic criteria set forth for DMby Bohan and Peter (I: polymyositis, II: dermatomyositis, III: myositis with malignancy, IV: childhood myositis, V: myositis with overlap syndromes) (8) should be altered to include a sixth diagnostic category, ADM. The rapidly progressive ILD has occurred in many DMpatients with mild muscle symptoms (2, 6) or slightly increased CPK levels (5, 7), but it is not clear whether or not all of such patients correspond to ADM. Anti-Jo-1 antibody is found in about 20% in PM/DMpatients and other types of antisynthetase antibodies, such as anti-PL-12, anti-OJ, are also found (16).…”
Section: Discussionmentioning
confidence: 99%